Silent Polio Transmission: A Spatial Analysis. (4th October 2017) - Jarvis, Christopher; Altamirano, Jonathan; Sarnquist, Clea; Garcia-Garcia, Lourdes; Reyes, Leticia Ferreyra; Montero-Campos, Rogelio; Cruz-Hervert, Luis Pablo; Holubar, Marisa; Talib, Aisha; Purington, Natasha; Halpern, Meira; Behl, Rasika; et al.
Abstract: Background: As wild poliovirus is eradicated and countries switch from Oral Polio Vaccine (OPV) to Inactivated Polio Vaccine (IPV) per WHO recommendations, preventing circulation of vaccine-derived poliovirus is a top priority. However, spatial dynamics of OPV transmission are not well understood. Understanding these trends will improve resource targeting in the event of OPV reintroduction in undervaccinated communities. Mexico provides a natural environment to study OPV as it provides IPV routinely and bi-annual OPV campaigns. Methods: Children in three villages near Orizaba, Mexico were randomized to three levels (10%, 30%, 70%) to receive OPV. We measured distance to nearest OPV shedding, and the amount of shedding close to unvaccinated individuals. We used maps to show the proximity and amount of shedding. Distance and density of shedding was analyzed separately using mixed effects logistic regression with random effects for household and time, adjusted for age, gender, area, and running water. Results: The median distance to nearest OPV shedding was 85 meters (IQR 46, 145). The median number of shedding individuals within 200m was 3 (2, 6). Shedding and between household transmission occurred rapidly with unvaccinated individuals shedding on day one of the study (Figure 1). There was little evidence (Odds Ratio [OR] 1.04 (95% Highest Posterior Density [HPD] 0.92, 1.16)) of an association between distance (per 100 m) from OPV shedding and odds of shedding. There was some suggestion that the number of OPV shedding within 200 m may have some effect on unvaccinated shedding with OR 0.93 (HPD 0.·84, 1·01) but not at 100 or 500m. Results were consistent across the three villages. Conclusion: Household structure appears to have limited value in predicting transmission of poliovirus shedding. The use of OPV results in rapid but low levels of transmission throughout the community and this would usually go undetected. The only way to avoid this is to not use OPV or to have strong controls such as quarantine, or strict hygiene protocols. After withdrawal of OPV worldwide the decision to reintroduce due to an outbreak should not be taken lightly as it appears a small amount of OPV is needed to result in transmission. Disclosures: All authors: No reported disclosures.